RESPON GENOTIPE KEDELAI BIJI BESAR DAN UMUR GENJAH TERHADAP KOMPLEKS HAMA PENGISAP POLONG - Bayu, Marida Santi Yudha Ika; Krisnawati, Ayda; Adie, M. Muchlish (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2017)
Response of large seed size and early maturing soybean genotypes against pod sucking bugs complex. Pod sucking bugs (Hemiptera: Pentatomidae) is the most detrimental pest on soybean in Indonesia. These pest attacks caused the decreasing of quality and quantity of yield as well as decreased seed germination. The use of resistant varieties is an alternative control which is environmentally friendly. The objective of this study was to determine the response of various soybean genotypes against pod sucking complex in the field. The experiment was conducted on June to September 2015 in Pasuruan, East Java. The treatment was arranged in randomized block design, 16 treatments with three replicates. The treatment consists of 14 soybean promising lines (G 511 H/Anj//Anj///Anj-11-2, G 511 H/Anjasmoro-1-6, G 511 H/Anj//Anj///Anj-7-1, G 511 H/Anjasmoro//Anjasmoro-5-1, G 511 H/Argom//Argom-2-1, G 511 H/Anjasmoro-1-4, G 511 H/Anjasmoro-1-2, G 511 H/Anjasmoro//Anjasmoro-2-8, G 511 H/Arg//Arg///Arg///Arg-12-15, G 511 H/Anj// Anj///Anj-6-3, G 511 H/Arg//Arg///Arg///Arg-19-7, G 511 H/Anjasmoro-1-7, G 511 H/Anj//Anj///Anj////Anjs-6-7, G 511 H/Anjasmoro-1-4-2), and two varieties (Anjasmoro and Grobogan). The results showed that the differences in soybean genotypes significantly influence the intensity of damaged pod and seed caused by pod sucking bugs. The intensity of damaged pod was 29.8?64.0% per plant. The intensity of damaged seed was 13.2-63.9% per plant. The number of puncture was 1.2-1.6 punctures per pod and 0.6-2.7 punctures per seed. Based on the intensity of damaged pod and seed, genotipe G 511 H/Anjasmoro//Anjasmoro-2-8, G 511 H/Anjasmoro-1-2, and G 511 H/Anjasmoro-1-6 were indicated consistently as moderately resistance against pod sucking complex. Those three genotypes could be use as a source of genes to improve the resistance of soybean against pod sucking bug.